Studi Evaluasi Kesiapan Strategi Pengembangan Ekonomi Kreatif Pemberdayaan Kesejahteraan Keluarga (PKK) di Kecamatan Tabanan - Setiawan, I M Dedy; Dananjaya, IGAN; Suparyana, PK (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
One of the efforts that can be done to remain productive, especially in the community in Tabanan District, is to intensify the development of the creative economy through PKK with certain strategies. However, in its implementation it is not yet known to what extent the level of readiness of the development strategy to be implemented, so the aim of this study is to determine the readiness of the PKK creative economy development strategy in Tabanan District based on the CIPP evaluation model. The research sample used purposive random sampling technique as many as 48 people. Data were collected using interview techniques, document study, and questionnaires, which were then analyzed using Z scores, T scores, and the Glickman Quadrant. The results showed that the context, input, and process components resulted in a positive category (+ - +) which means that the PKK creative economy development strategy in Tabanan District is ready to be implemented.